INTEGRASI KONSEPTUAL KEPEMIMPINAN PANCASILA, KEPEMIMPINAN MELAYANI, DAN LITERASI DIGITAL ALUMNI PELATIHAN KEPEMIMPINAN PENGAWAS KOTA PONTIANAK - Zainuri, Zainuri; Abidin, Didih (Komunitas Manajemen Kompetitif, 2025)
The focus of this research is the post-evaluation of the Pontianak City Government Supervisory Leadership Training (PKP) held by the Pontianak City Civil Service and Human Resources Development Agency (BKPSDM) in 2023-2024. The variable studied was the impact of the PKP. The research applied a descriptive method, a quantitative approach, and an evaluation design. The population of all PKP alumni from 2023-2024 was 70 people using a total sampling technique. There were 66 alumni respondents and 61 mentors. The results showed that the integration of Pancasila leadership, servant leadership, and digital literacy resulted in significant changes in the leadership behavior of supervisory officials. This research empirically proves the effectiveness of a structured and contextual PKP program. Support from mentors, stakeholders, and team members is a supporting factor. Limited human resources, internet infrastructure, and the speed of digitalization policy changes require continuous intervention. The research produces four recommendations for further research and strengthens the theory of integrated leadership. Bureaucratic practitioners need to redesign leadership development programs in the Indonesian public sector with a more holistic and integrated approach.